Immunohistochemistry of deparaffinised sections using antigen retrieval with microwave combined pressure cooking versus immunofluorescence in the assessment of human renal biopsies. Issue 5 (9th March 2013) - Shi, Suozhu; Zhang, Ping; Cheng, Qingli; Wu, Jie; Cui, Jing; Zheng, Ying; Bai, Xue-Yuan; Chen, Xiangmei
Abstract : Background: Immunofluorescence of frozen tissue sections (IF-F) is a traditional technique used in renal biopsy. However, IF-F has certain disadvantages, such as a few or even no glomeruli in the section, and limited long-term preservation of the fluorescently labelled samples. Methods: We compared two-step immunohistochemistry (IHC) staining of deparaffinised sections for antigen retrieval with microwave combined high-pressure cooking to IF-F used to detect antigens of IgG, IgA, IgM, C3, C1q, κ and λ in patient renal biopsy samples. The number of glomeruli detected, sensitivity and specificity of positive staining, tissue structure, and location staining of the antigens were determined using the two methods in 285 patients diagnosed with different renal diseases. Results: Concordant observations between IF-F and IHC were 99% for all antigen staining (1969 of 1995 observations) and 100% for IgG, IgA and IgM (all 285 observations). The number of glomeruli in IHC sections was significantly greater compared with IF-F sections (p<0.001). IHC provided clearer images of tissue structure, more precise localisation of positive-staining antigens, and IHC staining allowed simultaneous evaluation of tissue by light microscopy. Correlation between tissue structure and immune deposits are not readily attained by IF-F. Conclusions: IHC is superior to IF-F for immunopathological diagnosis of renal biopsy tissue and is a reliable replacement for the more traditional IF-F method.